High School teacher education throughout the 20th century Portugal: procedures and discussions: processos e debates (Revista Internacional de Formação de Professores, 2022)
How was the education of high school teachers in key-moments of the 20th century? What were the mainchanges brought about by these different epochs?
Keywords: Teaching profession. Teacher education. Pedagogical culture. Pedagogical practice.